PENGARUH BERBAGAI JENIS BOKHASI TERHADAP PERTUMBUHAN DAN HASIL BAYAM GITI HIJAU - Haruna, Mega . S; Ansar, Muh.; Bahrudin, Bahrudin (AGROTEKBIS, 2017)
This study aims to determine the effect of various types of bokashi on growth and yield of spinach green giti. The study used Randomized Block Design with three replications. The treatments were several doses bokashi consisting of five levels i.e.: control, bokashi leaves of Gliricidia 40 t/ha, bokashi leaves johar 40 t/ha, bokashi leaves lamtoro 40 t/ha, and bokashi goat manure 40 t/ha. Each treatment were consists of three replicates so that there are 3 x 5 = 15 experimental units. Processing research data conducted by using ANOVA subsequent treatment effect was tested further by the least significant difference test. The results showed that the provision of various types of bokashi not significantly affect the number of leaves, plant height, stem diameter, leaf area, but the real impact on plant fresh weight. Key Words: Bokashi, Green Giti Spinach.